Outcome of Nexgen® fixed bearing and posterior stabilising total knee replacement - Mohammed Harris bin Anwarali Khan (Kulliyyah of Medicine, International Islamic University Malaysia, 2016)
Total knee replacement is among excellent advancement in medical treatment which gives good joint function and pain relief for degenerative diseases of joint. Total knee replacement means a degenerative knee or diseased knee changed with implant. Total knee replacement has been introduced in Malaysia since 1970. This procedure had been carried out since that. General objective of this study is to calculate outcome of patients who had undergone Nexgen® total knee replacement between years 2000 until 2015. The specific objectives of this study are to calculate survival analysis of the implant, to evaluate radiological outcome following total knee replacement, to evaluate the functional and knee score outcome following nexgen fixed bearing and posterior stabilising total knee replacement. Study population will include patients from Orthopaedic Departments, Hospital Tengku Ampuan Afzan. It is a retrospective study. Inclusion criteria are total knee replacement was done by the two senior surgeon and presence of a complete record. There are total of 367 total knee replacement involving 313 patients was done during the study period. 54 stage bilateral total knee replacement, 156 right and 103 left total knee replacements were performed. Exclusion criteria are patients with incomplete data/record for analysis. Assessment include radiological, functional and quality of life outcome. Functional outcome analysed using Oxford knee score questionnaires and SF-36 questionnaires. End-points of implant defined as surgery with removal and adding or interchange of implant. Radiological outcome was measured by calculating the femoral angle and tibial angle using anteriorposterior and lateral radiograph of knee on short film. The femoral angle should be about 95°. The tibial angle should be about 90°. The study comprised of 160 respondents with 179 knees, 22 males (13.8%) and 138 females (86.3%). This represents 48.8% of the primary total knee replacement during fifteen years period. 177 knees (98.8%) was diagnosed with osteoarthritis, gouty arthritis in 1 knee (0.6%) and rheumatoid arthritis in 1 knee (0.6%). Patients underwent staged bilateral total knee replacement are 19 patients and single total knee replacement are 141 patients. Ethnic makeup were chinese 78 (48.8%), malay 64 (40%) and indian 18 (11.3%). Average age of patient is 64.24 years. Prophylactic antibiotics were prescribed to all patients prior to surgery and continued post operatively for 5 days. Torniquets were used in all patients. Surgical approach was medial parapatellar approach in all cases. Functional and knee score post operatively was excellent and good. Mean range of movement of knee during study period was left 107.50 degree and right 106.49. Mean femoral flexion angle is 92.38 degree and mean tibial angle is 89.48 degree. Oxford knee score is described based on four category which are excellent (>41), good (34–41), fair (27–33), and poor (<27)3. Excellent outcome was shown by 101 patients, good outcome in 41 patients and fair outcome in 18 patients. In this study mean total SF 36 score is 80.99. Anova analysis showed that patients in younger age group have better physical function, physical health and better SF 36 score.